The prevalence of peripheral arterial disease in diabetic subjects in south-west Nigeria - Bolaji O. Oyelade; Akintayo D. OlaOlorun; Louis O. Odeigah; Isaac O. Amole; Olufemi S. Adediran (AOSIS, 2012)
Background: Peripheral arterial disease (PAD) is rarely sought for and generally underdiagnosed even in diabetics in developing countries like Nigeria. PAD is easily detected and diagnosed by the ankle-brachial index, a simple and reliable test. Objectives: To determine the prevalence of PAD in diabetic subjects aged 50-89 years and the value of ankle-brachial index measurement in the detection of PAD. Method: A cross-sectional descriptive study of 219 diabetic subjects aged 50-89 years was carried out. The participants were administered a pre-tested questionnaire and measurement of ankle-brachial index (ABI) was done. The ankle-brachial index < 0.90 was considered equivalent to peripheral arterial disease. Results: The overall prevalence of PAD was 52.5%. The prevalence of symptomatic PAD was 28.7% whilst that of asymptomatic PAD was 71.3%. There were a number of associations with PAD which included, age (p < 0.05), sex (p < 0.05), and marital status (p < 0.05). The use of the ankle-brachial index in the detection of PAD was clearly more reliable than the clinical methods like history of intermittent claudication and absence or presence of pedal pulses. Conclusion: The prevalence of PAD is relatively high in diabetic subjects in the southwestern region of Nigeria. Notable is the fact that a higher proportion was asymptomatic. Also the use of ABI is of great value in the detection of PAD as evidenced by a clearly more objective assessment of PAD compared to both intermittent claudication and absent pedal pulses.